Behavioral Styles of Path-Goal Theory: An Exercise for Developing Leadership Skills. (September 2016) - Phillips, Antoinette S.; Phillips, Carl R.
Path-goal theory is firmly established as a robust, comprehensive leadership model. Its applicability makes it attractive to students and practitioners alike. We have designed an exercise with two main goals: first, to help students better understand the path-goal behaviors (directive, supportive, participative, achievement-oriented), particularly those in which they feel weakest; and second, to provide practice modeling each behavior through generating explicit sample statements for the various behaviors that can be used in various leadership situations. The exercise is ideal for use by instructors of upper level or graduate organizational behavior or leadership classes, or in leadership training contexts. We provide focused discussion activities centered on situational diagnosis (when to use which behavior) and guidelines for conducting a behavioral styles exercise. Using the suggested video examples aids in teaching the concepts and is very helpful in preparing students for the exercise.